An Optimization Study of Hot Water Generation from Solar PV/T Boosted Heat Pump; Case Study of Kai Nakorn Hotel, Vientiane Capital, Laos PDR - Mungkhaly, Piyaphone; Polvongsri, Sarawut; Mongkon, Sulaksana (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
Kai Nakorn Hotel, Laos PDR has a demand for hot water with a temperature of 60 - 65 oC and an amount of 2,000 L/day for consumption. In the hot water production, a 20 kW heater coil was used resulting to 95.54 kWh/day of electricity consumption, which is a high energy use. Therefore, this research aimed to study an optimum size of the hot water production system from Solar PV/T Boosted Heat Pump for hot water use in the Kai Nakorn Hotel in order to reduce the amount of electricity consumption. The first part was testing the electrical and thermal performance of the Solar PV/T following Standard testing to simulate a performance prediction equation of a 330 Wp Solar PV/T. The results revealed that the thermal performance of Solar PV/T panels obtained FR(τα)e and FRUL equal to 0.4018 and 10.466 W/m2•oC, respectively. The averaged power generation efficiency of solar PV/T panel was 16 % and an empirical equation for prediction performance of hot water generation with Solar PV/T Boosted Heat Pump was obtained. In the second part of the study, the equations that were obtained from the first part of the study were used to create a mathematical model to design an optimized system and analyze the cost-effectiveness for choosing the appropriate size of the hot water use in hotel. The conventional hot water production system used an electric heater of 20 kW to produce 2,000 L/day hot water at a temperature of 60 - 65 oC. The results showed that the optimized system used 330 Wp solar PV/T with 12 panels together with a 17.8 kWth heat pump. The electricity consumption was able to reduce by 28,072.71 kWh/year, or equivalent to the electricity costs of 86,952.84 Baht/year. The investment was 604,180 Baht and the payback period was 7.13 years.